2019
DOI: 10.1073/pnas.1816247116
|View full text |Cite
|
Sign up to set email alerts
|

Structural, functional, and behavioral insights of dopamine dysfunction revealed by a deletion in SLC6A3

Abstract: The human dopamine (DA) transporter (hDAT) mediates clearance of DA. Genetic variants in hDAT have been associated with DA dysfunction, a complication associated with several brain disorders, including autism spectrum disorder (ASD). Here, we investigated the structural and behavioral bases of an ASD-associated in-frame deletion in hDAT at N336 (∆N336). We uncovered that the deletion promoted a previously unobserved conformation of the intracellular gate of the transporter, likely representing the rate-limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…Given our current findings that dDAT and Ric interact, and that DAergic Ric activity impacts DAT activity, surface expression, baseline DA-dependent behaviors, and AMPH sensitivity, it is likely that Drosophila is an orthologous model for studying the DAT/Rit2 interaction. Indeed, Drosophila has proven a powerful system to investigate AMPH-stimulated DAT efflux mechanisms 15,47,48,64 , as well as hDAT coding variants identified in ADHD and ASD 21,49,[68][69][70] . In the current study, Drosophila genetics enabled us to determine that Ric-mediated changes in behavior are, indeed, DAT-dependent, and not due to another Ric-mediated, DAT-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Given our current findings that dDAT and Ric interact, and that DAergic Ric activity impacts DAT activity, surface expression, baseline DA-dependent behaviors, and AMPH sensitivity, it is likely that Drosophila is an orthologous model for studying the DAT/Rit2 interaction. Indeed, Drosophila has proven a powerful system to investigate AMPH-stimulated DAT efflux mechanisms 15,47,48,64 , as well as hDAT coding variants identified in ADHD and ASD 21,49,[68][69][70] . In the current study, Drosophila genetics enabled us to determine that Ric-mediated changes in behavior are, indeed, DAT-dependent, and not due to another Ric-mediated, DAT-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it reflects the absence of common risk variants. Several rare coding DAT variants with functional deficits both in vitro and in vivo have been identified in patients with psychiatric disorders (Bowton et al, 2014;Campbell et al, 2019;Cartier et al, 2015;Davis et al, 2018;DiCarlo et al, 2019;Gowrishankar et al, 2018;Grunhage et al, 2000;Hamilton et al, 2013;Hansen et al, 2014;Herborg et al, 2018;Mazei-Robison et al, 2005;Sakrikar et al, 2012;Stewart et al, 2019;Wu et al, 2015) but the causal link between these putative risk alleles and disease is still elusive as the family trees and cohort sizes have been too small for meaningful linkage or association analysis. We have, to the best or our knowledge, carried out the first association analysis of a coding DAT variant using large-scale exome data, and demonstrate a nominally significant association to bipolar disease.…”
Section: Discussionmentioning
confidence: 99%
“…DTDS typically presents in early infancy (Kurian, 1993;Kurian et al, 2011;; however, we recently identified an adult patient, who carries compound heterozygote missense mutations in SLC6A3 that only partially disrupt DAT function, and who suffers from an atypical form of DTDS with adult-onset of motor symptoms and comorbid neuropsychiatric disease (Hansen et al, 2014). The identification of this patient adds to several reports on heterozygous carriers of coding variants in SLC6A3 that have been diagnosed with neuropsychiatric disease including bipolar disorder, ADHD, and autism spectrum disorder (ASD) (Bowton et al, 2014;Campbell et al, 2019;Cartier et al, 2015;Grunhage et al, 2000;Hamilton et al, 2013;Mazei-Robison et al, 2005;Sakrikar et al, 2012). Most of these DAT variants show deficits in DAT properties and/or trafficking, and several cause behavioral changes in vivo, at least when homozygously expressed (Campbell et al, 2019;Cartier et al, 2015;DiCarlo et al, 2019;Hamilton et al, 2013;Hansen et al, 2014;Herborg et al, 2018; Mazei- Robison et al, 2005;Mergy et al, 2014;Sakrikar et al, 2012;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is evident from the case of a congenital mutation in the dopamine transporter involving a single residue deletion ΔN336 in the IL3 of the transporter that results in a transport defective mutant leading to autism spectrum disorder. This deletion, induces the formation of a previously unobserved half-open inward-facing (HOIF) conformation that is transport inactive (Campbell et al, 2019).…”
Section: Dynamics Of the Intracellular Gatesmentioning
confidence: 99%